0132 EFFECTS OF FOOD RESTRICTION ON STABILITY AND FRAGMENTATION OF DAILY ACTIVITY RHYTHMS. (28th April 2017) - Li, P; Patxot, M; To, T; Escobar, C; Buijs, RM; Hu, K
Abstract: Introduction: Locomotor activity in rodents displays robust daily/circadian rhythms in synchrony with light/dark cycles. Restricted feeding (FR) in a fixed and limited time period each day also affects daily activity rhythms, causing increased activity a few hours before the feeding period — food anticipatory activity (FAA). Here we tested whether FR during the dark phase affects the stability and fragmentation of daily activity rhythms, as mediated through the dorsomedial hypothalamic (DMH) nucleus — a neuronal node involved in the FAA. Methods: Locomotor activity was collected under 12h:12h light-dark cycles from18 Wistar rats in three groups. (Group 1) Six intact rats had ad libitum food access for >2 weeks. (Group 2) Six intact rats underwent a 16-day FR protocol in which food was only available between Zeitgeber time (ZT) 6–8 h. (Group 3) Six rats with the DMH lesion (DMHx) underwent an ad-lib protocol of >12 days followed by a 16-day FR protocol. Inter-daily stability (IS) and intra-daily variability (IV) were calculated using the last 7 days under each condition. To determine whether FR affects activity patterns outside the FAA-feeding period, IS and IV after excluding data between ZT3-8h were also obtained. Results: In the intact rats, FR caused a decrease of 15.7%±5.3%(SE) in IS (p=0.015) and an increase of 58.6%±15.5% in IV (p=0.0036). The FR effects remained after excluding the 5-hour FAA-feeding period. The DMH lesion did not affect IS and IV with ad-lib food access (both p >0.1). In the DMHx rats, FR did not affect IS (p>0.1) and caused an increase of 29.5% (±10%) in IV (p = 0.037). But the FR effect on IV disappeared when excluding the FAA-feeding period (change=8.5%±6.5%; p>0.1). Conclusion: Restricted feeding during the inactive phase leads to unstable and fragmented daily activity patterns across the 24 hours. Lesioning the DMH eliminates these FR effects. Support (If Any): This work was supported by NIH grants R00HL102241, R01AG048108 and P01AG009975 (to K.H.). P.L. was supported by the International Postdoctoral Exchange Fellowship 20150042 from the China Postdoctoral Council.